Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1186/s13756-017-0281-1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological bactericidal fast-acting effects of peracetic acid, a high-level disinfectant, against Staphylococcus aureus and Pseudomonas aeruginosa biofilms in tubing

Abstract: BackgroundThe bactericidal effect of disinfectants against biofilms is essential to reduce potential endoscopy-related infections caused by contamination. Here, we investigated the bactericidal effect of a high-level disinfectant, peracetic acid (PAA), against Staphylococcus aureus and Pseudomonas aeruginosa biofilm models in vitro.Methods S. aureus and P. aeruginosa biofilms were cultured at 35 °C for 7 days with catheter tubes. The following high-level disinfectants (HLDs) were tested: 0.3% PAA, 0.55% ortho-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 30 publications
(30 reference statements)
1
8
0
1
Order By: Relevance
“…This indicates that PAA treatment 249 impacts the outer membrane of M. psychrotolerans cells and that the level of damage might depend on PAA concentration. Some studies revealed that the PAA treatment 251 generates cell surface irregularities and partial grooves, with the damage becoming 252 increasingly apparent as the sanitizer concentration is increased (Chino et al, 2017;253 Ujimine et al, 2017;Park et al, 2013;Mustapha and Liewen, 1989). We did not 254 observe any grave damage to M. psychrotolerans cell morphology after 20 ppm PAA 255 treatment.…”
Section: Sem Analysismentioning
confidence: 60%
“…This indicates that PAA treatment 249 impacts the outer membrane of M. psychrotolerans cells and that the level of damage might depend on PAA concentration. Some studies revealed that the PAA treatment 251 generates cell surface irregularities and partial grooves, with the damage becoming 252 increasingly apparent as the sanitizer concentration is increased (Chino et al, 2017;253 Ujimine et al, 2017;Park et al, 2013;Mustapha and Liewen, 1989). We did not 254 observe any grave damage to M. psychrotolerans cell morphology after 20 ppm PAA 255 treatment.…”
Section: Sem Analysismentioning
confidence: 60%
“…Guidelines and in vitro studies indicate potential differences in efficacy between detergents, [45][46][47][48][49] disinfectants, 48,50,51 and AERs. 52 In the current study, contamination was not shown to be dependent on reprocessing characteristics, which is in line with another multicenter study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, S. aureus does not form spores or flagella, but possesses a capsule, can produce golden yellow pigment, and decompose mannitol (Tayeb-Fligelman et al, 2017). Additionally, it has also been found that tests of plasma coagulase, lactose fermentation and deoxyribonuclease are positive in S. aureus (Chino et al, 2017;Tayeb-Fligelman et al, 2017).…”
Section: Staphylococcus Aureusmentioning
confidence: 99%